IMPACT OF MISMANAGEMENT AND EMBEZZLEMENT OF PUBLIC FUNDS ON GOVERNMENT PARASTATALS - El Yaqub, A.B.; Ibrahim Musa; Sule Magaji (Universitas Agung Podomoro, 2024)
This study examines the impact of mismanagement and embezzlement of public funds in government parastatals using Federal Inland Revenue Service (FIRS), Abuja as a case study. The study employs the survey descriptive research design. A total of 85 respondents were selected as the sample size comprising staff of Federal Inland Revenue Service (FIRS), Abuja. Seventy-one (71) responses were validated from the survey. The findings reveal that the nature of mismanagement and embezzlement of the funds in the public sector is prevalent at (β = 0.912, R2 = 0.948, P = .000) and show that there are factors that enhance mismanagement and embezzlement of the fund in the government parastatals at (β = 0.892, R2 = 0.937, P = .000). It is found that mismanagement and embezzlement have a significant effect on the public fund in government parastatals (β = 0.887, R2 = 0.936, P = .000). It is also found that the extent to which financial irregularities and corrupt practices affect public service delivery (β = 0.896, R2 = 0.952, P = .000). Therefore, the study recommends the establishment of a strong penal code system to enforce laws and rules as sternly as the need for adequate punishment for offenders on corruption and related matters on fund embezzlement is paramount and germane.